Aldosterone is associated with left ventricular hypertrophy in hemodialysis patients - Feniman De Stefano, Greicy Mara Mengue [UNESP] (2016)
Objectives: Patients with chronic kidney disease present a higher degree of left ventricular hypertrophy than expected for hypertension levels. In chronic kidney disease the plot between the quotient extracellular water/total body water and aldosterone is shifted up and to the right. There are few studies that verified the role of aldosterone in cardiac remodeling in this set of patients. The aim of this study was to evaluate the relationship between serum aldosterone and left ventricular mass index in patients with chronic kidney disease on hemodialysis. Methods: The patients were submitted to clinical and laboratory evaluation, bioelectrical impedance, echocardiography and ambulatory blood pressure monitoring. The 27 patients included were divided into two groups according to aldosterone level and compared with each other. Results: The group of patients with higher aldosterone levels had higher left ventricular mass index. These groups were heterogeneous with regard to ambulatory systolic blood pressure, body mass index, and aldosterone levels and homogeneous with regard to the quotient extracellular water/total body water, renin-angiotensin-aldosterone system blockers, beta blocker use and other clinical characteristics. The association between aldosterone levels and left ventricular mass index was adjusted to confounding variables by a multiple linear regression analysis in which aldosterone was independently associated with left ventricular mass index. Conclusion: The data presented are consistent with a pathogenic role of aldosterone in left ventricular hypertrophy in patients with chronic kidney dialysis in dialysis patients. Trial registration: ClinicalTrials.gov identifier: NCT01128101.